Discharge Against Medical Advice: A Qualitative Case Study: - Shafaghat, Tahereh; Jabbari, Alireza; Kavosi, Zahra; Hosseini, Seyed Mojtaba; Ayoubian, Ali; Aidun, Amir; Rahimi-Zarchi, Mohammad Kazem (Galen Medical Journal, 2016)
Background: The most important criterion for healthcare success is customers’ satisfaction. The number of patients leaving the hospital on their own decision or Against Medical Advice (AMA) can be a sign of their discontent and a problem with considerable importance. In this regard, the present study was designed aiming at evaluating the causes of AMA discharges at a hospital affiliated with Shiraz University of Medical Sciences. Materials and Methods: This is a qualitative study on all patients who were discharged AMA from the studied hospital during 3 months in 2012 (March 21 – June 21). Data were collected through telephone interviews. All interviews were written by the researcher and analyzed using grounded theory with thematic method. Results: The most frequent reasons for discharge AMA were classified into 3 general themes: issues related to hospital status, the staff and the patients. Additionally, the most frequent reasons causing discharge AMA were as follows; 1. Sense of recovery; 2. Failure to register discharge order despite verbal order, 3. Physicians and nurses’ inadequate care (technically); 4. Lack of informing the patients and their relatives as to the patient’s condition properly; 5. Crowded wards; 6. Lack of attention to patients by the staff (emotionally). Conclusion: It seems that if hospital managers want to reduce discharge AMA, it is better to consider the causes. Based on such causes, effective intervention can be implemented which may differ in terms of resource-consuming. [GMJ. 2016;5(1):31-41]